Effects of Ozonized Aloe Vera Oil on Full-Thickness Excision Wound Healing: In Vivo Study - Evan Sebastian Gunawan; Muhamad Thohar Arifin; Yuriz Bakhtiar; Yan Wisnu Pradjoko; Muhammad Nur (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Disruption to the healing process of these wounds will consume large resources and will often require long-term medical management. Aloe vera oil is rich in anthraquinone compounds, especially emodin and chrysophanol. Anthraquinones have potent anti-inflammatory effects, which have the potential to activate various growth factors and chemokines and initiate angiogenesis processes that play a major role in wound healing. The ability of ozone to trigger mild oxidative stress plays an important role in triggering a cascade of cytokines and chemokines, including the initiation of vascular endothelial growth factor (VEGF) proteins that play a role in the initiation of angiogenesis. Methods: This study is an in vivo experimental study. A total of 60 rats were divided into 10 treatment and control groups. The treatment group was given ozonized aloe vera oil 600 mg/mL, 1200 mg/mL and 1800 mg/mL. Furthermore, the assessment of VEGF and new blood vessel formation was carried out. Data analysis was performed using SPSS version 25 software with univariate and bivariate tests. Results: The administration of ozonized aloe vera oil was able to increase the expression of VEGF, and the number of new blood vessels in the excision wound tissue. Conclusion: Ozonized aloe vera oil is effective in promoting excision wound tissue repair in vivo.